Optimalisasi Peran Orang Tua Dalam Membimbing Anak Usia Dini di TK Radhatul Jannah Palembang - Fitriana Fitriana; Hest Wahyuni; Nandang Heryana (Forum Kerjasama Pendidikan Tinggi, 2020)
The service of training on the role of parents in guiding early childhood at Raudhatul Jannah Kindergarten Palembang for guardians of Raudhatul Jannah Kindergarten students in Palembang was held on November 12-14, 2020. This activity was held at Raudhatul Jannah Kindergarten which was attended by 25 people consisting of 13 people guardians of students, 2 kindergarten teachers and 10 administrators of the Raudhatul Jannah foundation. From the results of the training on the role of parents in guiding early childhood for guardians of TK Raudhatul Jannah Palembang, it is able to increase understanding of the role of parents in guiding early childhood. The indicators that show that this activity has gone well are as follows: First 95% of parents are able to explain how the role of parents in guiding early childhood. Second, 100% of participants stated that the training that was followed was useful in increasing the ability of parents to guide their children.